The moral field of advance directive and its regulation in Brazil - Monteiro, José Dimas D’Avila Maciel Monteiro; Bonamigo, Elcio Luiz; Nunes, Rui (Acta Bioethica, 2025)
Despite more than 50 years of existence and their recognized importance, advance directives (ADs) are still the subject of doubts and criticism. The original defect, the instability of decisions, and the argument of personal identity are some of them. In Brazil, this instrument is not regulated by federal law, although Resolution No. 1995/2012 of the Federal Council of Medicine and Resolution No. 41/2018 of the Ministry of Health are in force, contributing to its implementation and to studies in this area. This article proposes to 1st) investigate some doubts and criticisms about ADs, as they challenge their moral authority; 2nd) highlight the repositioning of ADs in the moral field; 3rd) suggest this moral field as a starting point for bioethical investigations on their regulation in Brazil. The approach was philosophical/bioethical (analytical), according to Aristotle’s position in Nicomachean Ethics on the scope of ethical research. It is concluded that ADs can be more robust and effective if their moral field is that of the circumstances, where the manifestation provides the person with moral choices and actions that operate in a grey area, allowing health professionals and their representatives to interpret their wishes according to each situation.